Precipitants of Acute‐on‐Chronic Liver Failure: An Opportunity for Preventative Measures to Improve Outcomes. Issue 2 (6th January 2020) - Cullaro, Giuseppe; Sharma, Rajani; Trebicka, Jonel; Cárdenas, Andrés; Verna, Elizabeth C.
Abstract : Acute‐on‐chronic liver failure (ACLF) is a feared complication that can develop at any stage of chronic liver disease. The incidence of ACLF is increasing, leading to a significant burden to both the affected individual and health care systems. To date, our understanding of ACLF suggests that it may be initiated by precipitants such as systemic infection, alcohol use, or viral hepatitis. The prevalence of these vary significantly by geography and underlying liver disease, and these precipitants have a varying impact on patient prognosis. Herein, we present a review of our current understanding of the precipitants of ACLF, including gaps in current data and opportunities for meaningful intervention and areas of future research.